COMPARATIVE CHARACTERISTICS OF THE EFFECTIVENESS OF DIRECT AND INDIRECT RESTORATIONS ON TEETH WITH DISCOLORATION - I.V. Zhyvotovskyi; Yu.I. Sylenko; M.V. Khrebor (Ukrainian Medical Stomatological Academy, 2019)
The rapid development of dental industry and constant improvement of technologies in production of basic dental materials contribute to the increase of the quality of rendering dental care with the obligatory consideration not only of functional but also aesthetic parameters during a patient's rehabilitation. However, there is still no precise indication for the use of metal-free structures for the qualitative and durable aesthetic restoration of the frontal group of teeth, white-pink aesthetics and prosthetic rehabilitation, taking into account changes in the parameter of biological width of the tooth and aesthetic criteria. The aim of the research is to improve the effectiveness of treatment of frontal group teeth with discoloration using direct and indirect restorations by evaluating and comparing the quality of restorations. Research materials and methods. For clinical substantiation and comparison of direct and indirect ceramic restorations with classical fixation and the proposed method of fixation on the heated composite, 90 patients with discoloration and defects of the crown of the front teeth, aged 18 to 65 years, were examined and treated. A comparative evaluation was carried out one year after the restoration was completed. The distribution of patients into clinical groups was as follows: the first group - patients who were treated by direct restorations, performed with light- polymer restorative material Estet X HD (Dentsply) (50 patients, 125 restorations); the second group embraced patients, treated with indirect ceramic restorations manufactured by the method of pressing high temperature ceramics (IPS Emax). The latter group was in turn divided into two subgroups, depending on the treatment method: 2A - patients with indirect fixation by conventional methods on the Dentsply dual-cure composite of Calibra production (20 patients, 70 veneers) and 2B - patients with fixation treated on the heated composite Gradia Direct by GC production (20 patients, 55 veneers). In order to evaluate the quality of prosthetics in patients with direct and indirect ceramic restorations (veneers) it has been determined the status of these restorations using the modified USPHS (United States Public Health Service; Ryge, G., 1980, 1981) criteria for the frontal teeth group. The obtained results were processed by the method of variational statistics using Student's test. Research results. During the clinical evaluation of direct restorations using the modified USPHS criteria for the frontal teeth group, the following complications were identified: tooth sensitivity was present in 5.6% of teeth, fractures, cracks, chips - in 20 restorations (16%); discrepancy between the color of restoration and the color of natural teeth - in 30 restorations (24%); the presence of defects in the texture of the surface - 30 teeth (24%). Impaired marginal adaptation was in 32 restorations, which amounted to 25.6%; loss of restoration gloss - in 66,4%, the presence of secondary caries - in 17 teeth (13,6%); deficiency of occlusal contact -in 13 restorations (10.4%), of approximate contact - in 17 restorations (3.6%). A detailed analysis of the condition of indirect restorations and clinical complications in the second group showed that the most common defects are impairment of marginal adaptation - 16 veneers (12.8%), impairment of the integrity of veneers due to fractures, cracks, chips - 6 (4.8%), inconsistency of color - 13 veneers (10.4%), the presence of surface texture defects - 0, secondary caries - 3 teeth (2.4%), the position of fixing cement - 4 veneers (3.2%). Impaired occlusal contact was observed in 1 tooth (8.8%). No changes in approximate contacts were detected. The total number of complications was 17%, which indicates the need to find the optimization approaches to treatment with these structures. Comparison of the status of indirect restorations, depending on the method of fixation by subgroups showed that the impaired integrity of veneers due to fractures, cracks, chips in subgroup 2A was detected in 4 teeth (5.7%), and in the subgroup 2B - in 2 teeth (3.6%). Color change in group 2A was observed in 12 teeth (17.1%), in group 2B - in 3 teeth (5.5%). Disorders of marginal adaptation in group 2A were observed in 12 teeth (17.1%), in group 2B - in 4 teeth (6.6%). Secondary caries was observed on 2 teeth (2.9%) in group 2A and in one patient in group 2B (1.8%). According to the criteria for evaluating the state of indirect ceramic restorations and recommended follow-up professional actions, the following estimates were established: 28% of restorations in the first group, 55.7% of restorations in group 2A, 85.5% of restorations in group 2B received an "excellent" rating; 33.6% of restorations in the first group, 25.7% in group 2A, 5.5% in group 2B received a "good" rating; a "satisfactory" rating was obtained by 11.2% of restorations in the first group, 11.7% in group 2A, 5.4% in group 2B. In the first group, 27.2% of restorations needed immediate replacement, 11.4% - in the second and 3.6% - in the third group. The total score for the first group was 3.87±0.07, for 2A - 4.26±0.12, p.05, for group 2B - 4.73±0,1, p1˂p,05, p2˂0,05. Conclusion. Thus, our studies of direct and indirect restorations after one year of use showed that the highest level of quality was observed in the group where indirect restorations (veneers) were manufactured, which were fixed on the heated Gradia Direct composite by GC production. The obtained results are confirmed by the statistical analysis. To evaluate the quality and duration of using direct and indirect structures with different types of fixation, it is advisable to carry out a long-term monitoring for up to 10 years.